MAGNETIC STUDY OF AN ANTARCTIC WEATHERING PROFILE ON BASALT: IMPLICATIONS FOR RECENT WEATHERING ON MARS - Chevrier V.; Mathé P.E.; Rochette P.; Gunnlaugsson H.P. (My University, 2006)
In order to better interpret the Martian surface weathering-related mineralogy, we focused on a relevant analogue of the Martian subsurface in terms of lithology and paleoclimate: the Jurassic-aged Ferrar dolerite (Priestley Glacier, Transantarctic Mountains), weathered in cold and dry climate. Together with chemical and mineralogical studies, rock magnetic properties were investigated and completed with Mössbauer measurements. Weathering of the decimetric block is evidenced by chemical profiles showing an increase in Fe content (from 10.5 in the core to 13 wt.% in the surface) and a decrease in Si (from 57 to 53 wt.%, respectively). According to mineralogical, thermomagnetic and hysteresis properties, the main opaque mineral is inherited titanomaghemite, with a concentration about 1%. Enhancement in low field magnetic susceptibility (from 4 · 10- 6 to 10 · 10- 6 m3/kg, respectively) and saturation magnetization (from 0.44 to 0.96 Am2/kg, respectively) indicates the neoformation of metastable maghemite. Neoformed red ferric (oxy)hydroxides are abundant in the surface. High field susceptibility normalized to iron concentration and Mössbauer spectra indicate a replacement of Fe2+ from primary silicates (pyroxene) by poorly crystalline antiferromagnetic Fe3+ (oxy)hydroxides. Thus, highly magnetic titanomaghemite and maghemite coexist with nanosized ferric (oxy)hydroxides and primary silicates, in accordance with Martian in situ observations. Therefore, this study supports the formation of the Martian regolith as resulting from a slow weathering process in near present day conditions. © 2006 Elsevier B.V. All rights reserved.
Keywords: ANTARCTICA; FERRAR DOLERITE; MARS; REGOLITH; ROCK MAGNETISM; WEATHERING; Jurassic; Mesozoic::Jurassic; Мезозой::Юрская